Cover Image. (11th October 2017) - Sawant, SS; Dongre, H; Ahire, C; Sharma, S; Kannan, S; Mahadik, S; Chaukar, D; Lukmani, F; Patil, A; D'Cruz, A; Vaidya, MM; Dongre, P
Abstract : The cover image, by SS Sawant et al, is based on the Research Article A nomogram for predicting the risk of neck node metastasis in pathologically node‐negative oral cavity carcinoma, DOI:10.1111/odi.12696 .